The moguls and the dictators : Hollywood and the coming of World War II - Welky, David 1971- (Johns Hopkins Univ. Press, 2008)
This author's analytical approach will be appreciated by historians as well as film buffs. He examines Hollywood's response to the rise of fascism and the beginning of the Second World War. Welky traces the shifting motivations and arguments of the film industry, politicians, and the public as they negotiated how or whether the silver screen would portray certain wartime attributes.